Un service de table en bronze et argent soigneusement rangé dans une cave à Reims/Durocortorum - Michaël Brunet; Fabienne Médard; Magalie Cavé; Stéphane Sindonino (Gallia)
The excavation of a domus cellar, carried out in Reims prior to the installation of the first tramway line, revealed an exceptional set of silverware, swaddled in cloth. The degree of alteration of the remains does not allow us to state with certainty the wealth of the domus to which this cellar belonged, but the proximity of three hypocausts, which were abandoned at the same time, suggests that it was associated with a comfortable Roman dwelling. The cellar is rectangular, with a rectilinear access hallway, in its northwestern corner. It measures over 6 m in length, including the cellar descent, and 3.85 m in width. The unequal state of conservation of the cellar (presence of intruding modern circulation networks and masonry recovery when the site was abandoned at the end of Antiquity) prevents us from establishing the presence or absence of wall openings. On the other hand, the burning of the remains allowed us to highlight installations visible within the cellar floor. Post holes may have supported a raised floor or set of shelves. A bench, raised to the geological chalk level along the western wall, would have housed a cubicle for storing crockery, though not indicative of hoarding. The quality of preservation of the wares, as well as of the fabrics, which reveal no traces of burning, unlike most of the other objects collected in the main cellar backfill, argue in favor of an enclosed compartment, which would have strongly isolated the assemblage from the fire and limited the effects of oxygen and microorganisms on the woven material. The metal wares set includes seven vessels, as well as three cochlearia and a ligula. With the exception of the four solid silver spoons, the rest are bronze dishes, either completely or partially coated with silver leaf, sometimes only the upper portion of the vessel. The plated silver leaf is relatively thick and espouses all the existing forms; on some objects it bears additional incised decorations. These, especially the beaded and pirouetted border on the two large, circular, polished dishes, are typical of silver tableware. Graffiti that are difficult to decipher are visible on several of the objects. The homogeneity of the dishes, the quantity of objects, as well as their impressive size –an average of thirty centimeters in diameter– are rare enough to be noteworthy. This group belongs to a middle range of wealth, between the simple bronze tableware and the more luxurious solid silver tableware produced in Italy. It was likely used for receptions and special occasions and was intended to illustrate the prosperity of its owners. The set is dated to between the end of the 2nd c. and the 3rd c. AD; the oval dishes, usually made of bronze, are the most characteristic items from this period. The ensemble comes from workshops located in central or central-eastern Gaul. In addition to the precious tableware, the most extraordinary phenomenon is the perfect state of preservation of the fabrics within which the pieces were wrapped. Their analysis made it possible to isolate four different types of fabric, based mainly on technical data (fabric orientation, presence of a border or selvedge, for example), as well as on weft decoration and choice of raw material. In the first three fabric categories, the raw material used was a linen of very fine quality. The fourth type is likely a material of vegetal origin, other than linen, unless it underwent a different treatment process. The study of the crockery organization alongside the textile data allows us to propose an overall reconstruction of the deposit. A layer of cloth isolated each of the vessels, and two silver spoons were also wrapped separately in cloth, suggesting that the owner of this table service wanted to minimize surface alterations due to rubbing between each object. Thus, the nearly useable state of the dinner service provides us with a very concrete glimpse into daily life within a Reims domus in the 3rd c.